Cruzipain promotes Trypanosoma cruzi adhesion to Rhodnius prolixus midgut. - Lívia Almeida Uehara; Otacílio C Moreira; Ana Carolina Oliveira; Patrícia Azambuja; Ana Paula Cabral Araujo Lima; Constança Britto; André Luis Souza dos Santos; Marta Helena Branquinha; Claudia Masini d'Avila-Levy (PLoS Neglected Tropical Diseases)
Background Trypanosoma cruzi is the etiological agent of Chagas' disease. Cysteine peptidases are relevant to several aspects of the T. cruzi life cycle and are implicated in parasite-mammalian host relationships. However, little is known about the factors that contribute to the parasite-insect host interaction. Methodology/principal findings Here, we have investigated whether cruzipain could be involved in the interaction of T. cruzi with the invertebrate host. We analyzed the effect of treatment of T. cruzi epimastigotes with anti-cruzipain antibodies or with a panel of cysteine peptidase inhibitors (cystatin, antipain, E-64, leupeptin, iodocetamide or CA-074-OMe) on parasite adhesion to Rhodnius prolixus posterior midgut ex vivo. All treatments, with the exception of CA074-OMe, significantly decreased parasite adhesion to R. prolixus midgut. Cystatin presented a dose-dependent reduction on the adhesion. Comparison of the adhesion rate among several T. cruzi isolates revealed that the G isolate, which naturally possesses low levels of active cruzipain, adhered to a lesser extent in comparison to Dm28c, Y and CL Brener isolates. Transgenic epimastigotes overexpressing an endogenous cruzipain inhibitor (pCHAG), chagasin, and that have reduced levels of active cruzipain adhered to the insect gut 73% less than the wild-type parasites. The adhesion of pCHAG parasites was partially restored by the addition of exogenous cruzipain. In vivo colonization experiments revealed low levels of pCHAG parasites in comparison to wild-type. Parasites isolated after passage in the insect presented a drastic enhancement in the expression of surface cruzipain. Conclusions/significance These data highlight, for the first time, that cruzipain contributes to the interaction of T. cruzi with the insect host.